Free will, quarantines, and moral enhancements: neuroabolitionism as an alternative to criminal law - Diego Borbón (Frontiers in Sociology, 2024)
This article critically navigates the complex debate surrounding free will and criminal justice, challenging traditional assumptions of moral responsibility and culpability. By exploring hard incompatibilism, which denies free will, I question the ethical justification of punitive sanctions and critically analyze the alternative models such as the public health-quarantine and nonconsensual neurobiological “moral” enhancements. These alternatives, however, introduce practical and ethical concerns. Advocating for a neuro-abolitionist perspective, through the proposition of five initial principles/debates, the article suggests a shift in integrating sociological abolitionism with insights from neuroscience. The discussion extends to the implications of hard incompatibilism and the pursuit of more humane and effective approaches to deviant behavior, ultimately calling for the abolition of punitive models and criminal law itself.